Production of porcelain parts by additive manufacturing - Duarte, Pedro Gonçalo Pereira (2023)
Additive manufacturing is a disruptive way to produce three dimensional objects with the main advantage being the ability to produce highly complex geometries and designs which are impossible or expensive to produce in other conventional way. With the fast development and growth of AM technologies the interest from the industry has grown. This is the case of Porcelanas da Costa Verde, a porcelain producer looking for new technologies that allow to reach new markets, produce new objects and improve its productivity. In this work two powder bed AM technologies were used: Binder Jet Printing (BJP) and Selective Laser Sintering (SLS). As BJP is already available at industrial facilities of Costa Verde, this technique was the main focus of these work. To accomplish so, the study of a proper in-bed binder, which allows the manipulation of the printed parts in postconformation processes was crucial. Among the in-bed binders studied (PVA, maltodextrin, sodium alginate and CMC), PVA exhibit the best results in amounts of 10 to 15 wt.% in the powder formulation. Once the in-bed binder was identified, the improvement in the printability of the powders, i.e., the ability to produce defect free printed parts was assessed by studying the use of heat-treated porcelain powders. The results shown that the use of equal fractions of raw and heat-treated porcelain powders leads to the elimination of defects in the printed parts. Concerning the use of post-conformation processes in order to improve the density of the produced parts, the thermal industrial cycles of Porcelanas da Costa Verde were studied and cold isostatic pressing (CIP) and pressureless infiltration of parts with porcelain suspension as well. The final results highlight the ability to produced complex shaped parts with the industrial thermal cycles, however, the full densification of the parts was not obtained. In the case of CIP, the final parts reached 97 % of relative density but shown to be not appropriate for complex shaped parts. In the case of the pressureless infiltration, the process shown to be not appropriate for the infiltration of porcelain printed parts. Finally, the industrialization of the techniques was explored with focus in the raw materials production and the post-conformation processes and both shown to be adequate for the industrialization. Concluding, the possibility of producing defect free porcelain objects through powder bed AM technologies was proven, however, several challenges were identified to be assessed in future work in order to reach full industrialization.